Pengaruh Profil Risiko Reksadana Terhadap Kecenderungan Perpindahan Investasi Reksana Pada Periode Krisis Tahun 2008 - , Asep Imat Ruhimat ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to analyze the impact of the mutual fund's risk profile against mutual funds flow during the financial crisis in 2008. The results showed that during this period, the average of equity mutual funds risk level higher than average risk of balanced mutual funds. At the same time, massive redemption has occured to equity mutual funds, conversely subscription of balanced mutual funds tend to increase. However, there was no correlation between the redemption of equity mutual funds against subscription in balanced mutual funds, therefore the mutual fund's risk profile has no impact on mutual funds flow during the period. The study also showed that there was no correlation between fluctuations in the Jakarta Composite Index (JCI) against fluctuations of balanced mutual funds, therefore the fluctuation of JCI cannot be used to predict the risk level of the balanced mutual funds.